VD_FINDINFO HC / 2020 / 550 vom 14. August 2020 - VD Tribunal cantonal (2020)
HONORAIRES, ARCHITECTE, CONTRAT D'ARCHITECTE, COMPENSATION DE CRÉANCES, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL | 120 al. 1 CO, 394 al. 3 CO, 398 CO, 404 al. 2 CO